Teaching metaphorical extensions of private events through rival‐model observation to children with autism. Issue 4 (20th September 2017) - Dixon, Mark R.; Belisle, Jordan; Munoz, Bridget E.; Stanley, Caleb R.; Rowsey, Kyle E.
Abstract : The study evaluated the efficacy of observational learning using the rival‐model technique in teaching three children with autism to state metaphorical statements about emotions when provided a picture, as well as to intraverbally state an appropriate emotion when provided a scenario and corresponding metaphorical emotion. The results provide a preliminary evaluation of how an observational teaching strategy may be effective in teaching children with autism to correctly tact emotions when given metaphors.